Metaphysical transcendence in Plotinus - or: How can we address absolute transcendence? - Rohstock, Max (Classical philology, 2025)
In the following article, I want to conduct an experiment: I ask what happens if we assume that Plotinus constructed transcendence radically. If we take transcendence seriously, however, the question arises as to what extent Plotinus can still address transcendence. This problem can only be solved if we clarify how Plotinus addresses transcendence. I show that Plotinus makes it possible to experience transcendence with the help of the “loving Intellect,” that is, henological striving. Thus, henological striving becomes the hinge of his metaphysics. Additionally, this striving reveals Plotinian metaphysics as a transcendental philosophical theory of subjectivity avant la lettre.
Gesehen am 22.10.2025